1978
DOI: 10.1090/s0002-9947-1978-0461648-4
|View full text |Cite
|
Sign up to set email alerts
|

On the number of real zeros of a random trigonometric polynomial

Abstract: Abstract. For the random trigonometric polynomial N 2 s,(/)cosn0, n-l where g"(t), 0 < / < 1, are dependent normal random variables with mean zero, variance one and joint density functionwhere A/-1 is the moment matrix with py = p, 0 < p < 1, i ¥*j, i,j m 1, 2.N and a is the column vector, we estimate the probable number of zeros.1. Consider the random trigonométrie polynomial N (1.1) (9) = $(t, 9) =% gn(t) cos n9, where g"(t), 0 < t < 1, are dependent normal random variables with mean zero, variance one an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…It is known that a "random" trigonometric polynomial of degree p has p/V3 zeros in [0,1) (see [7]), so one might guess that KQ = 1/\/3 ^ 0.5773... However this is not the case.…”
Section: Zeros Of Fekete Polynomials 867mentioning
confidence: 99%
“…It is known that a "random" trigonometric polynomial of degree p has p/V3 zeros in [0,1) (see [7]), so one might guess that KQ = 1/\/3 ^ 0.5773... However this is not the case.…”
Section: Zeros Of Fekete Polynomials 867mentioning
confidence: 99%
“…This shows they have significantly more zeros than algebraic polynomials. This number remains the same when we pass to the case of non-zero µ, see [7] or [17].…”
Section: Introductionmentioning
confidence: 78%
“…For example, Dunnage [4] studied polynomials T n = n k=1 a k cos k with a k s independent identically distributed standard normal random variables and estimated that a probable number of real zeros in the interval 0 ≤ ≤ 2 to be 2 √ 3 n + O n 11/13 log n 3/13 when n is large. Later, Das [3] considered the generalization T n = n k=1 a k b k cos k , where the a k s are also independent identically distributed standard normal random variables with b k = k p for p ≥ −1/2 and found that the expected number of real zeros in 0 ≤ ≤ 2 to be 2p+1 2p+3 1/2 2n + O √ n for large n. Sambandham and Maruthachalam [8] obtained the same result for n large when the a k s are dependent random variables with constant correlation between any two of them. We refer the reader to [1,5] for detail results on random polynomials.…”
Section: Introductionmentioning
confidence: 99%